The Ethiopian Tort Law Vis-a-Vis Constantly Evolving Technology: An Empirical Analysis of Cyberspace and Product Defects Tort Liability - Silesh, Gizachew; Endale, Mamenie; Bitew, Yenew; Bitew, Yenew (Bahir Dar University Journal of Law, 2023)
Book IV, Title XIII, of the 1960 Ethiopian Civil Code governs the three categories of tortious liabilityâ€”fault-based liability, strict liability, and vicarious liabilityâ€”and the quantum and modalities of compensation. This law has existed for the last seven decades without significant revision. Consequently, one might hypothesize that Ethiopia’s vast majority of tortious liability provisions must be more responsive to contemporary development. Hence, there are efforts to incorporate tort provisions in different legislations of the country, including the 1995 FDRE constitution, the 2005 FDRE Criminal Code, the Computer Crime Proclamation No. 958/2016, the Freedom of the Mass Media, and the Access to Information Proclamation No. 590/2008 (as amended by the Media Proclamation No. 1238/2021). Despite this, legal scholarship still needs to give tort law issues the proper attention they deserve. There needs to be more research outputs and a comprehensive analysis of Ethiopian tort law. Evidence-based research and recommendations in addressing the gaps in tort law contribute to policymakers addressing existing problems and serve as input to the revision of Book VI-Title XII of Ethiopia’s Civil Code of 1960 on extra-contractual liability. Accordingly, this study attempts to show the legal loopholes in Ethiopian tort law regarding cyberspace torts and product liability as a case study. A triangulation of doctrinal and empirical qualitative research approaches is employed for data collection. The researchers employed document analysis, desk review, and semi-structured interviews with the relevant stakeholders to collect primary data. The researchers consulted relevant books, journals, periodicals, reports, and newspapers as secondary data sources. The finding shows that the 1960 Ethiopian Civil Code needs to be updated to administer tort liabilities caused by cyberspace and product liability. Concerning cyberspace torts, it fails to regulate online gambling and defamation, pop-up advertising, cybersquatting, spamming, and other cybers mearing tortious liabilities. By now, cryptocurrencies in Ethiopia are operating in the gray area of the law, which results in tortious liability. It needs careful revision to regulate product defects arising from 3D printing and autonomous driving. Therefore, the study recommends reforming the existing tort law in Ethiopia to bring it up to date with emerging developments such as cyberspace torts and product defects.